An Interdisciplinary Team-Based Learning Experience in Health Systems and Inequalities - Erik Black; Catherine Striley; Richard Davidson; Wayne McCormack (Association of American Medical Colleges, 2014)
Abstract This team-based learning experience was designed to addresses issues associated with health systems and inequalities. This content should be considered introductory. Team-based learning was adopted as an instructional methods based on its ability to promote discourse and involvement and to accommodate the limited number of faculty facilitators at our disposal. The resource includes an individual readiness assurance test, a team readiness assurance test, and an application exercise. Average performance across professions ranged from 16.5 to 20.27 on a 28-point scale. The mean team performance significantly exceeded (p < .01) individual mean performance. There was no statistically significant difference in team readiness assurance test score between teams (p = .37).